Ask & tell, just don't perform: military discourses of (in)security and sexual identity. - Shelbourn, Maurianna Goodrich (Kansas State University, 2012)
The military operates through a system of gender and sexuality hierarchies that privilege masculinity and heterosexuality as the ideal category of service member. This symbolic national institution is also conceptually tied to notions of citizenship. For marginalized groups, gaining the ability to freely enlist in the military represents a benchmark toward achieving full and equal status as political subjects. Such has been the case for the mainstream lesbian, gay, bisexual, and transgender rights movement. For much of the past century, military discourses have aided in rhetorically constructing homosexual identities as pathological, deviant, and unfit to serve in the armed forces. A recent shift in this rhetoric from Department of Defense (DoD) officials, which contributed to a repeal of the “Don’t Ask, Don’t Tell” policy, calls into question how changing discourses about gay and lesbian service members rhetorically construct queer citizenship. To answer this question, theories of gender and sexuality performance, corporeal rhetoric, and critical security discourse inform an analysis of the Report of the Comprehensive Review of the Issues Associated with a Repeal of “Don’t Ask, Don’t Tell”, a DoD document assessing potential risks to the military upon repeal. The analysis reveals that despite assertions made in the document that open service by gay men and lesbians poses minimal threat, this claim is ultimately grounded in the presumption that institutional hegemony adequately constrains performative possibilities for LGB identity articulation.
Ask and tell, just don't perform
Keywords: Sexual identity; Militarism; Gender identity; Don't ask, don't tell; Communication (0459)